Pharmacokinetic Properties and Human Use Characteristics of an FDA‐Approved Intranasal Naloxone Product for the Treatment of Opioid Overdose. (10th June 2016) - Krieter, Philip; Chiang, Nora; Gyaw, Shwe; Skolnick, Phil; Crystal, Roger; Keegan, Fintan; Aker, Julie; Beck, Melissa; Harris, Jennifer
Abstract: Parenteral naloxone has been approved to treat opiate overdose for over 4 decades. Intranasal naloxone, administered "off label" using improvised devices, has been widely used by both first responders and the lay public to treat overdose. However, these improvised devices require training for effective use, and the recommended volumes (2 to 4 mL) exceed those considered optimum for intranasal administration. The present study compared the pharmacokinetic properties of intranasal naloxone (2 to 8 mg) delivered in low volumes (0.1 to 0.2 mL) using an Aptar Unit‐Dose device to an approved (0.4 mg) intramuscular dose. A parallel study assessed the ease of use of this device in a simulated overdose situation. All doses of intranasal naloxone resulted in plasma concentrations and areas under the curve greater than those observed following the intramuscular dose; the time to reach maximum plasma concentrations was not different following intranasal and intramuscular administration. Plasma concentrations of naloxone were dose proportional between 2 and 8 mg and independent of whether drug was administered to 1 or both nostrils. In a study using individuals representative of the general population, >90% were able to perform both critical tasks (inserting nozzle into a nostril and pressing plunger) needed to deliver a simulated dose of naloxone without prior training. Based on both pharmacokinetic and human use studies, a 4‐mg dose delivered in a single device (0.1 mL) was selected as the final product. This product can be used by first responders and the lay public, providing an important and potentially life‐saving intervention for victims of an opioid overdose.